PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS NILAI-NILAI KEPEDULIAN UNTUK PEMBELAJARAN MEMBACA SISWA KELAS III A SD NEGERI 106836 LIMAU MANIS - Nidiya Kharismah; Beta Rapita Silalahi (Yayasan Pendidikan Islam dan Multikultural, 2021)
This study aims to develop a picture story book based on caring values ​​for learning to read for class III SD Negeri 106836 Limau Manis. This study uses the Borg and Gall development model according to Sugiyono which consists of five stages, namely potential and problems, data collection, product design, design validation, design revision. The data collection technique used in this development is in the form of a questionnaire. Data analysis techniques used are qualitative data analysis techniques and quantitative data analysis techniques. The results of the study show that picture story books based on caring values ​​for grade 3 elementary school students are feasible to use. The assessment according to the Indonesian language expert lecturer got an average score of 4.82 with a category (very good) and from class III A teachers got an average score of 4.76 with a category (very good) from both Indonesian language expert validators and class III A teachers can be totaled on average The average score is 4.79 in the